ANALISIS PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, DAN CITRA MEREK TERHADAP KEPUASAN PELANGGAN KORAN KOMPAS (STUDI PADA PELANGGAN KORAN KOMPAS DI WILAYAH SEMARANG) (Students' Journal of Economic and Management, 2014)
Entering the era of globalization at the moment, many companies print media like newspapers compass offer variance the same product make competition gets tougherA reasonableness if the company which are at the hyper competition as currently preparing a variety of activities to defend itself in the market, in order to remain in existence maintain consumers, even get new consumer, so that each company can perform the omnipresence with serious to won the competition.Specifically this research talk about customer satisfaction newspaper of the compass in the region of Semarang.This research test three independent variable that is the quality of the product perception of the prices of and the image of a brand that could affect the customer satisfaction.The aim of this research is to mengananalisis the influence of third the independent variable the newspaper to customer satisfaction of the compass in the region of semarang.There are three hypothesis advanced by as follows: the quality of the product influential positive and significantly to customer satisfaction, perception the price of influential positive and significantly to customer satisfaction, the image of a brand influential positive and significantly to customer satisfaction.The study is done with a method of a questionnaire to 150 customers newspaper of the compass in the region of semarang obtained by using the method of sampling, pursosive where researchers have criteria or a specific purpose against samples will be examined.A sample in this research is now consumers who has been subscribing to a newspaper compass.Testing in this research using analysis linear regression worship of idols.The result of this research stated that the quality of the product and perception the price of influential positive and significantly to customer satisfaction, while to image a brand not affect the customer satisfaction.Keywords: product quality, price perception, citra brands, and customer satisfaction